Shari’ah principles of sukuk structure in Malaysia Islamic capital market - Kamaluddin, Norlela; Ab. Manan, Siti Khadijah; Sufian, Fadzlan; Htay, Sheila (Faculty Of Business Management, Uitm Terengganu, 2012)
Malaysia as the pioneer of Sukuk has captured the global Sukuk’s share market in Islamic capital market tremendously and has played an important role for the remarkable development of Sukuk. Malaysia has a successful track record in innovating and commercializing many Shari’ah-compliant products. The MICM product innovation and world first achievements from 1990 to 2008 are the evidence of important role and achievement of MICM domestically and globally, for instance the issuance of First Global Corporate Sukuk Ijarah in 2001. The Sukuk markets have used many shari’ah principles to facilitate their functions, namely; profit sharing principles of Mudarabah and Musharakah; sale based principles of Murabahah, Bai’ Bithaman Ajil, Salam and Istisna’; and hire purchase principle of Ijarah. Consequently, these principles are employed to develop the Sukuk market’s instruments such as Asset-Backed Securities - Islamic Medium-Term Notes (ABS-IMTN), Islamic Medium-Term Notes (IMTN) and Islamic Commercial Papers (ICP).